2015
DOI: 10.1039/c4cp05353b
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations of ammonium-based protic ionic liquids: steric effects on structure, low frequency vibrational modes and electrical conductivity

Abstract: Protic ionic liquids (PILs) are of great interest as electrolytes in various energy applications. Molecular dynamics simulations of trialkylammonium (with varying alkyl group such as methyl, ethyl, and n-propyl) triflate PILs are performed to characterize the influence of the alkyl group on the acidic site (N-H) of the ammonium cation. Spatial distribution function of anions over this site on the cation reveals significant influence of the length of alkyl tail on intermolecular structure. Vibrational density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 48 publications
4
41
3
Order By: Relevance
“…The FF MD approach gives no IR signal below 200 cm −1 . As a side remark we note that Sunda et al 57 reported FF MD simulations of power spectra (vibrational density of states) for triethylammonium triflate, which showed only one band in region of 100 to 200 cm −1 .…”
Section: Ir Spectramentioning
confidence: 65%
“…The FF MD approach gives no IR signal below 200 cm −1 . As a side remark we note that Sunda et al 57 reported FF MD simulations of power spectra (vibrational density of states) for triethylammonium triflate, which showed only one band in region of 100 to 200 cm −1 .…”
Section: Ir Spectramentioning
confidence: 65%
“…It should be mentioned, however, that the MD relaxation processes appear to be significantly slower as compared to the experiment. This a major drawback of non-polarizable force fields 28 , 38 , 39 . Moreover, while a sum of several exponents is a good approximation for the QENS intermediate scattering functions, the corresponding MD curves are decidedly “stretched”, requiring, for example, Kohlrausch-Williams-Watts (KWW) functions for modeling.…”
Section: Resultsmentioning
confidence: 99%
“…3b and c) at $4 Å corresponds to hydrogen bonding interactions between the acidic hydrogen attached to nitrogen (H N ) and oxygen atoms of the SO 3 À group (of [TfO À ] anions or Naon) within the rst solvation shell. The N-S RDF peak at $5.5 Å arises due to the weak hydrogen bonding interactions between methyl/methylene hydrogen atoms of [dema + ] and oxygen atoms of the SO 3 À group as shown in the atomistic simulation study by Sunda et al 27 on [dema][TfO] PIL. The peak intensity of N-S RDF decreases with an increase in PIL concentration.…”
Section: Radial Distribution Functionsmentioning
confidence: 98%
“…The Molecular Dynamics (MD) simulation study by Sunda et al 26 on benzyltrialkylammonium triuoromethanesulfonate ILs has shown that the presence of C-H/phenyl interactions has a pronounced effect on ionic conductivity. Subsequently, Sunda et al 27 examined the inuence of steric effects on dynamics of ammonium triate PILs by varying the alkyl groups (methyl, ethyl, and n-propyl) on the ammonium cation. The authors concluded that an increase in the alkyl tail length leads to a decrease in electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%